Efficient Radiolabeling of Block Copolymer Micelles through Radiometal Salt Precipitation for Theranostic Applications. Issue 9 (15th July 2022) - Liu, Huanhuan; de Kruijff, Robin M.; Laan, Adrianus C.; Beekman, Freek J.; van den Heuvel, Eline; Ramakers, Ruud M.; Eelkema, Rienk; Denkova, Antonia G.
Abstract: A variety of polymer micelles are designed for the delivery of chemotherapeutic drugs to tumors. Although the promise of these nanocarriers is very high, in the clinic the effectivity is rather limited. Determining the in vivo fate of the micelles can greatly help to improve this treatment. Here, a simple and fast chelator‐free method for radiolabeling of polymer micelles composed of different block copolymers is presented, which can allow evaluating the behavior of the nanocarriers in vivo using noninvasive nuclear imaging techniques (e.g., single photon computed tomography, SPECT). The radiolabeling method consists of adding the radioisotope ions, i.e., 111 In(III), resulting in a high radiolabeling efficiencies up to 90%. The results suggest that the radiolabeling efficiency depends on two important factors: the properties of the hydrophobic block in the block copolymer composing the micelle core, and the speciation of the radiometal salts. The formation of metal hydroxides and their precipitation in the core of the micelles appears to be a key factor for high stability. Moreover, the method can be applied to radiolabel the micelles in the presence of chemotherapeutic drugs. Finally, a SPECT study shows that the radiolabeled samples are stable in vivo without any evident loss of 111 In(III). Abstract : This work describes an easy and chelator‐free method for radiolabeling polymeric micelles with radionuclides. Rather than attaching to the surface of the nanocarrier, the radiometals precipitate in the core of the micelles, which preserves the inherent surface characteristics of the micelles. An in vivo experiment reveals that the radiolabeled particles possess excellent stability.